Evaluasi Kompetensi Guru dalam Pelaksanaan Pembelajaran Bahasa Indonesia - Farahdila, Nonika; Wagiran (Cipta Media Harmoni, 2025)
Good learning management can support the achievement of learning objectives. With optimal classroom management, teachers can adjust learning models and methods according to learning objectives and student needs, so that the learning process becomes more effective and meaningful. However, teacher competence in learning activities still needs to be evaluated. This study aims to evaluate the competence of Indonesian language teachers in implementing learning using the Teacher Competency Assessment tool (APKG-2). This study is descriptive evaluative with data taken from two videos of Indonesian language teacher learning practices. The data collection method was carried out through documentation of learning practices and assessments were carried out by two observers using APKG-2 which included three main aspects: opening activities, core activities, and closing activities. The results of the study showed that teacher competence was included in the